Ceramic Total Knee Arthroplasty: Ready to Go? - Solarino, G.; Piconi, C.; De Santis, V.; Piazzolla, A.; Moretti, B. (Joints, 2017)
Total knee arthroplasty (TKA) is a well-established surgical procedure in the late stages of knee osteoarthritis. Nevertheless, this procedure is associated with a percentage of unsatisfactory results and biomechanical failures, with aseptic loosening being the most common cause of revision. Beside these problems, cutaneous and systemic hypersensitivity reactions to metals have arisen as an increasing concern after joint arthroplasties, even if allergies against implant materials are still a quite rare and not well-known problem. Ceramic composites have been recently used in prosthetic components, showing minimum wear and excellent long-term results in total hip replacement, due to their high resistance to scratching and their better wettability with respect to cobalt–chromium alloy. Furthermore, the biologic response to debris generated from these bearings is less aggressive. Knee joint simulator tests and clinical results demonstrate promising results of TKAs with ceramic components that should led to benefit for the patients.
Keywords: knee replacement; arthroplasty; ceramic composite; metal; hypersensitivity